Conducta obstétrica en primigesta de 20 años con 22.2 semanas de gestación con diagnóstico de shock séptico. - Granizo Pazos, Laura Leticia (2022)
Sepsis is a clinical syndrome characterized by biological, biochemical and organic alterations that can lead to multiple organ failure and death. It is caused by an infectious process of the organism, in pregnant women it is associated with urinary tract infections, pyelonephritis and chorioamnionitis. Worldwide, septic shock is among the ten leading causes of death in the general population, in pregnant women it is estimated that cases of bacteremia, sepsis and septic shock correspond to 0 to 12%. The present clinical case that is analyzed corresponds to a 20-year-old primigravida patient transferred to the General Hospital from a Hospital with a lower level of care with a diagnosis of pregnancy of 22.2 weeks plus septic shock, the respective assessment was carried out in the emergency area, the gynecologist on duty decides her admission to hospitalization and she is managed by an antibiotic scheme, whose applied obstetric behavior is timely and efficient because it was oriented towards treating the cause and daily follow-up was provided, so a favorable evolution was presented.